Hospital pedagogy: One student, one case - de Menezes Dal Col, Marcela; Pereira Ribeiro, Caroline; Klein Stein, Maria Rita (Guará Journal, 2019)
The objective of this study is to understand the importance of education for specific cases of hospitalized children and adolescents for their development and how pedagogy, in this case, teachers, must adapt to the diverse conditions encountered in these cases. Through qualitative research, with a structured guide, observations were conducted in a hospital setting, focusing on a specific case with numerous special educational needs. This article mentions four different categories present within the hospital classroom and related to the issues of the case study: the complexity of the educational process for a hospitalized student, multiple perspectives on the importance of education in hospitals, the knowledge and methods of teachers, and the relationships between family, teacher, hospital, and student.